2018
DOI: 10.1038/s41598-018-28516-5
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 (TLR4) Expression Affects Schwann Cell Behavior in vitro

Abstract: Peripheral nerve injury can result in the decreased quality of life and bring us economic burden on society and individuals. Wallerian degeneration (WD) is critical for nerve degeneration and regeneration, but the mechanisms of WD are still elusive. Here, we report the effect of Toll-like receptor 4 (TLR4) on cultured Schwann cells (SCs) in vitro. The data showed that TLR4 expression was up-regulated after sciatic nerve injury of rat. TLR4 was expressed in cultured SCs. Enhanced or silenced expression of TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The experimental procedure was employed as described previously (9). In short, the cells were resuspended in DMEM at a concentration of 5 Â 10 4 cells/ well.…”
Section: Transwell Cell Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedure was employed as described previously (9). In short, the cells were resuspended in DMEM at a concentration of 5 Â 10 4 cells/ well.…”
Section: Transwell Cell Migration Assaymentioning
confidence: 99%
“…Insight into its intrinsic mechanism reveals that E6020, a novel synthetic toll-like receptor 4 (TLR4) agonist, is capable of accelerating infiltration of SCs and remyelination in the rat spinal cord (8). TLR4 is expressed both in innate immune cells and in central nervous system cells, and has been reported to participate in nervous system development and modulate the adult neuronal precursor cell differentiation and proliferation (9). Recently reported study has offered proof that the expression of TLR4 can affect lipopolysaccharide (LPS)-induced inflammatory cytokine production by SCs (10).…”
Section: Introductionmentioning
confidence: 99%
“…Pain reduction in patients with PNI is an important area of focus in medicine. Previous studies have demonstrated that Schwann cells serve an important role in promoting axonal regeneration, myelin repair and functional recovery in neuroregeneration (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide-induced inflammatory cytokine production by SCs is dependent upon TLR4 expression. In vitro data showed that TLR4 expression is upregulated after sciatic nerve injury of rat and modulation of its expression increased relative gene expression of proinflammatory molecules such as c-Jun and extracellular signal-regulated kinase (ERK) [32]. In our in vitro model, TRIAM reduced significantly TLR4 expression implying an anti-inflammatory potential of SCs after TRIAM treatment.…”
Section: Discussionmentioning
confidence: 80%